2009
DOI: 10.1017/s0950268809990379
|View full text |Cite
|
Sign up to set email alerts
|

Biennial hyperepidemic shigellosis in an observant Jewish community

Abstract: We aimed to study patterns of shigellosis in a large observant Jewish community in Israel and to describe local interventions during outbreaks. Surveillance data from the Ministry of Health were used to calculate incidence rates in 1998-2006, both in the city of Bene Beraq and the Tel Aviv district. Information on isolates was collected from the bacteriological laboratory of a community hospital. Public notices and educational conferences conveyed a message to increase personal hygiene and keep ill children at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…There have been limited studies on winter patterns of shigellosis seasonality, and they have failed to clearly identify the mechanism underlying these winter patterns [ 37 , 38 ]. From 1978–1988, winter patterns of shigellosis seasonality were observed in Milwaukee, United States and were attributed to the lack of appropriate sanitary control in daycare centers in major cities during the winter [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been limited studies on winter patterns of shigellosis seasonality, and they have failed to clearly identify the mechanism underlying these winter patterns [ 37 , 38 ]. From 1978–1988, winter patterns of shigellosis seasonality were observed in Milwaukee, United States and were attributed to the lack of appropriate sanitary control in daycare centers in major cities during the winter [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Provided that the same protocol is used, it allows comparison of strains detected in different outbreak. The genetic relatedness of the strains in this study provides strong evidence that this cluster was a single outbreak and associated with recurrent endemic shigellosis in Israel [10,12].…”
Section: Discussionmentioning
confidence: 97%
“…showed that between 1998 and 2006, outbreaks of shigellosis followed a biennial pattern in Israel with annual rates that ranged from 18 to 353 cases per 100,000 population [12]. Also in 2009 outbreaks of S. sonnei in Israel were still continuing [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shigellosis outbreaks are cyclical within the UOJC in Montréal, having occurred at different intensities at approximately 1-to 5-year intervals ( Table 5) [2][3][4][5][6][7][8][9]. The regular recurrence of shigellosis in the UOJC is caused by the spread of the infectious agent as a result of travel to other similar communities with high prevalence of the disease or through chronic carriers who serve as a reservoir (2,5,10). The periodicity of Shigella outbreaks in the UOJC may be due to persistent low endemicity that generates an outbreak when a new cohort of young children with no previous shigellosis enters daycare or school (3).…”
Section: Discussionmentioning
confidence: 99%